The living death of antiquity - Fitzgerald, William (Oxford University Press, 2022)
The Living Death of Antiquity' examines the idealization of an antiquity that exhibits, in the words of Johann Joachim Winckelmann, 'a noble simplicity and quiet grandeur'. Fitzgerald discusses the aesthetics of this strain of neoclassicism as manifested in a range of work in different media and periods, focusing on the late eighteenth and early nineteenth centuries. In the aftermath of Winckelmann's writing, John Flaxman's engraved scenes from the0Iliad and the sculptors Antonio Canova and Bertel Thorvaldsen reinterpreted ancient prototypes or invented new ones. Earlier and later versions of this aesthetic in the ancient Greek Anacreontea, the French Parnassian poets and Erik Satie's Socrate, manifest its character in different media and periods. Looking with a0sympathetic eye on the original aspirations of the neoclassical aesthetic and its forward-looking potential, Fitzgerald describes how it can tip over into the vacancy or kitsch through which a 'remaindered' antiquity lingers in our minds and environments. This book asks how the neoclassical value of simplicity serves to conjure up an epiphanic antiquity, and how whiteness, in both its literal and its metaphorical forms, acts as the 'logo' of neoclassical antiquity, and functions aesthetically0in a variety of media. In the context of the waning of a neoclassically idealized antiquity, Fitzgerald describes the new contents produced by its asymptotic approach to meaninglessness, and how the antiquity that it imagined both is and is not with us.
Keywords: Satie; Erik; Canova; Antonio; Thorvaldsen; Bertel; Flaxman; John; Leconte de Lisle; Pope; Alexander; Socrate; Aesthetics; Neoclassicism (Art); Sculpture; Neoclassical; Rezeption; Ästhetik; Antike; Klassizismus